4
$\begingroup$

In the quantum textbook I'm currently working from, the completeness relation is written as:

$$ \sum_i |\psi_i \rangle \langle \psi_i| = \mathbb{1}. $$

But this seems to specifically require knowledge of individual bra and ket vectors. I know wavefunctions are supposed to satisfy both orthogonal and completeness relations, but I thought wavefunctions were written as coefficients of vectors $ \langle x | p \rangle = \psi(x) $ rather than the vectors themselves. Is there a way of writing the completeness relations if we're only given wavefunctions rather than bra or ket vectors? For example, the orthgonal relation for normalized wavefunction $ \psi_i $ and $ \psi_j $ is:

$$ \int_{-\infty}^\infty \psi^*_i(x) \psi_j(x) dx = \delta_{ij}. $$

But I'm unsure of the equivalent for the completeness relation. Any insight would be greatly appreciated!

$\endgroup$

2 Answers 2

11
$\begingroup$

One way you can show the completeness relation without bra-ket notation is just $$\sum_{i} \langle \psi_i , v \rangle \psi_i = v \qquad \forall v\in\mathcal{H},$$ where $\mathcal{H}$ is the Hilbert space in question, and $\langle \cdot,\cdot\rangle$ is the corresponding inner product.

Or you can say that the linear operator $$\begin{cases} T:\mathcal{H} \rightarrow \mathcal{H}\\[7pt] v \mapsto T(v)=\sum_{i} \langle \psi_i , v \rangle \psi_i\end{cases} $$ is the identity operator $T = 1\!\!1$.

$\endgroup$
6
$\begingroup$

The completeness relation reads: $$\sum_{I=1}^{\infty} \psi^{*}_{I}(x') \psi_{I}(x)=\delta(x'-x ).$$ Proof: Suppose any wave function $\Psi$ can be expanded using the $\psi_i$: $$ \Psi(x)=\sum_{I=1}^{\infty} c_I \psi_I(x).$$ Taking inner product with $\psi_j$: $$\langle \psi_j, \Psi \rangle=\sum_{I=1}^{\infty} c_I \underbrace{\langle \psi_j, \psi_I \rangle}_{=\delta_{ij}} \implies \langle \psi_j,\Psi \rangle=\sum_{I=1}^{\infty} c_I \delta_{Ij}=c_j .$$ Plugging back into our expression, we obtain: \begin{equation} \Psi(x)=\sum_{I=1}^{\infty} \langle \psi_I,\Psi \rangle \psi_i(x). \end{equation} Using the definition of the inner product: \begin{equation} \Psi(x)=\sum_{I=1}^{\infty} \left(\int_{x'} \psi^{*}_{I}(x') \Psi(x') dx' \right) \psi_I(x). \end{equation} Exchanging the integral and the sum, ignoring the mathematical subtleties of why we are allowed to do so, we obtain the desired relation: $$\Psi(x)=\int_{x'} \left(\sum_{I=1}^{\infty} \psi^{*}_{I}(x') \psi_{I}(x) \right) \Psi(x') dx' \implies \sum_{I=1}^{\infty} \psi^{*}_{I}(x') \psi_{I}(x)= \delta(x'-x).$$ EDIT: Since someone was not satisfied with the answer, I give an alternative proof using only the expressions you mentioned. We start with the completeness relation in bra-ket notation: $$\sum_{I} |\psi_i \rangle \langle \psi_i| =\mathbb{1}.$$ Sandwich it between $|x' \rangle$ and $\langle x|$ to obtain: $$\sum_{i} \langle x|\psi_i \rangle \langle \psi_i| x' \rangle=\langle x| x' \rangle.$$ Using the properties of the inner product and that position eigenstates are orthonormal yields: $$\sum_{i}\langle x| \psi_i \rangle \left( \langle x'| \psi_i \rangle) \right)^{*}=\delta(x-x').$$ Finally, using the equation from the post that $\langle x| \psi_i\rangle=\psi_i(x)$, we have, as desired: $$\sum_{i} \psi_i(x) \psi_i(x)^{*}=\delta(x-x').$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.